2003
DOI: 10.1073/pnas.2033883100
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of nitric oxide on the heme iron and β-93 thiol of human hemoglobin during cycles of oxygenation and deoxygenation

Abstract: Nitric oxide has been proposed to be transported by hemoglobin as a third respiratory gas and to elicit vasodilation by an oxygenlinked (allosteric) mechanism. For hemoglobin to transport nitric oxide bioactivity it must capture nitric oxide as iron nitrosyl hemoglobin rather than destroy it by dioxygenation. Once bound to the heme iron, nitric oxide has been reported to migrate reversibly from the heme group of hemoglobin to the ␤-93 cysteinyl residue, in response to an oxygen saturation-dependent conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 45 publications
2
56
0
2
Order By: Relevance
“…The reactivity of S-nitrosylated Hb depends on the redox valency state, the ligation state of the hemes, and the number of SNO/Hb (5,12,37,(47)(48)(49). SNO-Hb standards previously used in triiodide assays (40)(41)(42)(43)(44)(45)(46) were synthesized with a large excess of low-molecular-weight SNO, which produces SNO-Hbs with Ϸ2 SNOs per tetramer; heme valency and ligation states of the standards were not characterized, and the samples were not assayed at physiological ratios of SNO/Hb. As an initial validation, we synthesized stock solutions of SNO oxyHb (50-100 M SNO/100 M Hb as assayed by photolysis; Ϸ15% Met) and verified under these conditions that amounts of SNO when measured by photolysis, triiodide, and Saville assays (39) were in good agreement (values by triiodide and photolysis were within 5%, P was not significant).…”
Section: See Also Triiodide Cautionary Notes In Si Text)mentioning
confidence: 99%
See 3 more Smart Citations
“…The reactivity of S-nitrosylated Hb depends on the redox valency state, the ligation state of the hemes, and the number of SNO/Hb (5,12,37,(47)(48)(49). SNO-Hb standards previously used in triiodide assays (40)(41)(42)(43)(44)(45)(46) were synthesized with a large excess of low-molecular-weight SNO, which produces SNO-Hbs with Ϸ2 SNOs per tetramer; heme valency and ligation states of the standards were not characterized, and the samples were not assayed at physiological ratios of SNO/Hb. As an initial validation, we synthesized stock solutions of SNO oxyHb (50-100 M SNO/100 M Hb as assayed by photolysis; Ϸ15% Met) and verified under these conditions that amounts of SNO when measured by photolysis, triiodide, and Saville assays (39) were in good agreement (values by triiodide and photolysis were within 5%, P was not significant).…”
Section: See Also Triiodide Cautionary Notes In Si Text)mentioning
confidence: 99%
“…In this assay, biological samples are placed in acid plus triiodide to liberate NO. Other reagents [potassium ferricyanide (FeCN), potassium cyanide, N-ethylmaleimide (NEM), sulfanilamide (SAA), and mercurous chloride] are incorporated to selectively eliminate or block formation of one or another NO species (41)(42)(43)(44)(45). For example, pretreatment of biological samples with FeCN (3-200 mM followed by desalting) is reported to selectively remove NO from hemes, and SAA/HCl is reported to selectively eliminate nitrite; NEM and cyanide supposedly stabilize SNOs by blocking reactive thiols and hemes, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Gladwin and co-workers did not find evidence for the allosteric cycling of NO from the heme iron to the β93 Cys residues and they determined that generation of Cys-modified Hb did not influence the reaction kinetics [20][21][22]. These experiments were not supportive of the allosteric cycling model, and suggested that β93 Cys plays a minor role in the regulation of NO activity by Hb.…”
Section: Introductionmentioning
confidence: 97%